Screening and characteristics of ammonia nitrogen removal bacteria under alkaline environments - Zhang, Rui; Luo, Liang; Wang, Shihui; Guo, Kun; Xu, Wei; Zhao, Zhigang (Frontiers in Microbiology, 2022)
The toxicity of ammonia nitrogen (AN) has always caused severe harm to aquatic animals in intensive aquaculture conditions, especially in saline-alkali aquaculture waters. The application of AN removal bacteria is a safe and effective method for controlling the AN concentration in aquaculture water through direct conversion to bacterial protein. However, there is still a lack of AN removal bacteria that are appropriate for saline-alkali aquaculture conditions. In this study, three AN removal strains were screened out under alkaline conditions from the alkali-tolerant strains distributed in carbonate saline-alkali soil and water environments in Northeast China, including Bacillus idriensis CT-WN-B3, Bacillus australimaris CT-WL5-10 and Pseudomonas oleovorans CT-WL5-6. Under different pH (8.0-9.0), salinities (10-30 g·l-1 NaCl), alkalinities (10-30 mmol·l-1 NaHCO3) and AN concentrations (1-3 mg·l-1), corresponding to the actual conditions of saline-alkali aquaculture waters, the AN removal rates and relative charecteristics of these strains were analyzed. The results showed that all of the three strains were efficient on AN removal under various conditions, which highest removal rate reached up to 3×10-13 mg·cfu-1·h-1. Both CT-WL5-10 and CT-WL5-6 were most efficient under pH 9.0 with 3 mg·l-1 initial AN, while pH 8.5 with 2 mg·l-1 AN was the best fit for CT-WN-B3. In 96-h pure incubation of these strains in alkali media, approimately 90% AN were removed, and pH values were decreased of 2.0 units within 12 h accompanied with the growth of the strains. In addition, salinity and alkalinity slightly disturbed the removal rates of CT-WL5-10 and CT-WL5-6, but there were at least 65% AN removed by them within 24 h. These results indicated that all the three strains have well application prospect in saline-alkali aquaculture waters.